Identification of multi-drug resistant Acinetobacter baumannii phage YZ2 and evaluation of its therapeutic efficacy in vivo and in vitro - Zhi, Yaru; Yan, Dongmei; Tang, Qinfang; Xiao, Lihua; Cai, Aiting; Sun, Mingzhong; Chen, Hongmei; Wang, Yungang; Fu, Qingping (Frontiers in Microbiology, 2025)
IntroductionCarbapenem-resistant Acinetobacter baumannii (CRAB) has recently become an important pathogen in clinically acquired infections, making treatment more challenging.MethodsThe treatment of bacterial infections may improve with the development of phage therapy and phage-antibiotic combination therapy. Here, we reported a novel phage YZ2 that has a double-stranded DNA genome of 40,181 bp with 37.93% GC content. A total of 46 open reading frames (ORFs) and no virulence or antimicrobial resistance genes were annotated in the genome of phage YZ2. Phage YZ2 is a novel member of the Autographiviridae, with a latency period of approximately 20 min and a burst size of approximately 134 phage particles per infected host cell.ResultsThe in vitro antibacterial results demonstrated that YZ2 could rapidly eliminate host bacteria at a low multiplicity of infection, showing strong bactericidal efficacy. In vivo, YZ2 significantly increased the survival rate of A. baumannii-infected Galleria mellonella larvae from 10 to 100% within 72 h.DiscussionMoreover, compared with the use of phage or polymyxin B alone, the combined use of phage YZ2 and polymyxin B can significantly increased the survival rate of G. mellonella larvae and had a synergistic effect. These results imply that phage YZ2 has the potential for development as an antimicrobial agent.